Celebrity Endorser, E-Wom dan Harga yang Kompetitif terhadap Keputusan Pembelian Secara Online - Lidyawati Munawaroh; Bayu Wijayantini; Wahyu Eko Setianingsih (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the effect of Celebrity Endorser, E-WOM and competitive prices on online purchasing decisions for Ms Glow consumers at @msglowjemberid. The research method is descriptive quantitative. This study uses multiple linear regression analysis techniques to test the independent variables on the dependent variable. The sample used was 160 respondents. The results showed that Celebrity Endorser had a positive and significant effect on online purchasing decisions of 0.326. E-WOM has a positive and significant effect on online purchasing decisions of 0.456. While the price has a positive and significant effect on online decisions on Ms Glow consumers by 0.726. Through the coefficient of determination test, it is proven that Celebrity Endorser, E-WOM and Price influence purchasing decisions on Ms Glow consumers at @msglowjemberid by 66.4%, while 33.6% comes from other variables that are not in this study. In conclusion, the three variables, namely Celebrity Endorser, E-WOM and Price, have a positive and significant effect on online purchasing decisions for Ms Glow consumers at @msglowjemberid. Keywords: Celebrity Endorser, E-WOM, Price, Online Purchase Decision